2009
DOI: 10.1016/j.jmarsys.2007.04.010
|View full text |Cite
|
Sign up to set email alerts
|

On the morphological long-term development of dumped material in a low-energetic environment close to the German Baltic coast

Abstract: The development of the bed bathymetry of an experimental dumping area was followed over three and a half years by means of multibeam echosounder techniques. Two types of material were discharged in the bight of Mecklenburg in the Baltic Sea in approximately 20 m of water depth. One set of the discharges was 2900 m³ of glacial till and the other set was a 2400 m³ mixture of glacial till, sand and minor amounts of cohesive matter. Only approximately 2500 m³ (86 %) of the glacial till and 1500 m³ (63 %) of the mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 16 publications
(14 reference statements)
0
6
0
1
Order By: Relevance
“…The majority of the dredged material disposal sites have not been characterised, up until the present time; as such, their extent and distribution have been essentially unknown. The distinctive`ring-likeś tructures of these sediments reflect the transfer of vertical, into horizontal, momentum when the disposal hits the seabed (Stockmann et al, 2009). It could be inferred that the applied shear stress was insufficiently high to enhance erosional processes of the coarser material.…”
Section: Seascapes On the Continental Shelfmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the dredged material disposal sites have not been characterised, up until the present time; as such, their extent and distribution have been essentially unknown. The distinctive`ring-likeś tructures of these sediments reflect the transfer of vertical, into horizontal, momentum when the disposal hits the seabed (Stockmann et al, 2009). It could be inferred that the applied shear stress was insufficiently high to enhance erosional processes of the coarser material.…”
Section: Seascapes On the Continental Shelfmentioning
confidence: 99%
“…Even if marine sand extraction is very limited in Spain, such material disposal sites reduce the availability of such sediment resources for beach nourishment. Dumping areas should be monitored during future surveys, with repetition sampling intervals of several years, as the observed processes occur slowly (Stockmann et al, 2009). …”
Section: Seascapes On the Continental Shelfmentioning
confidence: 99%
“…그러나 이 연구들은 단 빔음향측심기 또는 천부탄성파 자료를 통한 2차적인 연구로 제한되었으며, 실질적인 층면구조를 파악하기 위한 기술적 한계를 가지고 있다. 그러나 최근 십여 년 동안 고정밀 위치정보 시스템과 함께 고정밀 다 중빔음향측심기술이 해저지형 연구에 많이 적용되었 다 (Knappen and Hulscher, 2002;Wienberg et al, 2004;Wienberg and Hebbln, 2005;Thornton et al, 2006;Kubicki et al, 2007;Li and King, 2007;Stockmann et al, 2009 (Flemming, 1988). (Fig.…”
Section: 서 론unclassified
“…Indeed, Lepland et al (2009) observed restricted spread of dumped mixture of mud, sand and gravel, and loadinginduced compaction of underlying natural organic-rich mud at a dumping site in Oslofjord, Norway. Stockmann et al (2009) and Tauber (2009) observed minimal change in the volume of experimentally dumped mounds of glacial till and mixed till, silt and sand, but modest smoothing of the surface roughness by reworking of fine-grained material to local depressions and the development of sandy lags on local elevations during 3 years in the Mecklenburg Bight, southern Baltic Sea.…”
Section: Introductionmentioning
confidence: 97%